2022
DOI: 10.1098/rstb.2021.0394
|View full text |Cite
|
Sign up to set email alerts
|

Risks to biodiversity from temperature overshoot pathways

Abstract: Temperature overshoot pathways entail exceeding a specified global warming level (e.g. 1.5°C or 2°C) followed by a decline in warming, achieved through anthropogenically enhanced CO 2 removal from the atmosphere. However, risks to biodiversity from temperature overshoot pathways are poorly described. Here, we explore biodiversity risks from overshoot by synthesizing existing knowledge and quantifying the dynamics of exposure and de-exposure to potentially dangerous temperatures for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…For example, healthy ecosystem functioning mediates human adaptation, but ecosystems are themselves also directly affected both by the compound climate impacts 151 , 152 and by human responses to them. 153 , 154 Examples from this review highlight that human responses depend on healthy and functioning ecosystems. 86 , 97 , 107 , 127 Deeper understanding of how such interactions affect climate risk and adaptation therefore merits further research.…”
Section: Resultsmentioning
confidence: 99%
“…For example, healthy ecosystem functioning mediates human adaptation, but ecosystems are themselves also directly affected both by the compound climate impacts 151 , 152 and by human responses to them. 153 , 154 Examples from this review highlight that human responses depend on healthy and functioning ecosystems. 86 , 97 , 107 , 127 Deeper understanding of how such interactions affect climate risk and adaptation therefore merits further research.…”
Section: Resultsmentioning
confidence: 99%
“…But the urgency of avoiding critical values in global average temperature is illustrated by the analysis of long-term biodiversity trends. When this path is simulated using available data from 30 000 species (with given tolerance thresholds when exposed to warmer conditions) it is found that major damage to biodiversity will take place [ 101 ].…”
Section: Biodiversity Adaptation and Engineeringmentioning
confidence: 99%
“…According to the European Union Commission for climate action, CO 2 produced by human activity is the largest contributor to global warming . The global average temperature has already risen by 1.1 °C above preindustrial (pre-1750) levels and may rise up to 2.1–3.5 °C by 2100 unless tougher mitigation action is taken . Moreover, the natural cycle of carbon is being disrupted by human activities such as deforestation and degradation of tropical forests, which already account for roughly 12% of total anthropogenic greenhouse gas emissions and dominate the national CO 2 emission profile of developing countries such as Brazil and Indonesia …”
Section: Introductionmentioning
confidence: 99%
“…1 The global average temperature has already risen by 1.1 °C above preindustrial (pre-1750) levels and may rise up to 2.1−3.5 °C by 2100 unless tougher mitigation action is taken. 2 Moreover, the natural cycle of carbon is being disrupted by human activities such as deforestation and degradation of tropical forests, which already account for roughly 12% of total anthropogenic greenhouse gas emissions and dominate the national CO 2 emission profile of developing countries such as Brazil and Indonesia. 3 The endergonic conversion of CO 2 into value-added chemical fuels (e.g., CO, CH 4 , CH 3 OH) is one of the most promising ideas to address global warming and store renewable energy.…”
Section: ■ Introductionmentioning
confidence: 99%